Predicting the volume of slope failure material using the 2-dimensional limit equilibrium method - Santoso, Hendra (2022)
Mining operations in areas with the potential for landslides require careful analysis of the risks that will occur so that the consequences of losses can be anticipated early with the approach to predicting the volume of landslide material. This study aims to evaluate and predict materials that are at risk of slope failures on the slopes of the PT. TMR mining located in Bengalon East Kutai District of East Kalimantan Province. The method used is to collect geological data, soil shear strength parameters and earthquake factors and the influence of groundwater on the body of the slope. Estimation of the predicted volume of slope failures based on the area of each slip surface is calculated using the prismoidal cross section method and multiplied by the probability of slope failures. The results show estimated volume of 122,298 m3 if the slope failure is caused by saturated slope conditions and 2,438 m3 if the slope failure is caused by a semi-saturated slope. © Published under licence by IOP Publishing Ltd.